«Sealed» with the Holy Spirit (Eph 1,13-14) and Circumcision - Ferda, Tucker S. (2012)
Most studies of Eph 1’s «sealed with the promised Holy Spirit» have tried to articulate the Christian ritual or experience that the sealing metaphor describes, such as baptism, confirmation, charismatic gifts, etc. This article, however, refocuses on the theological logic of vv. 13-14 to argue that, regardless of the Christian rite described, the author here explicates that rite by referring to circumcision with the use of the verb «sealed». The argument includes the insight that the description of «sealed» in Eph 1,13-14 corresponds to other texts that describe circumcision as a final step in Jewish proselytism.
Keywords: Ephesians 1,13-14; Confirmation; Circumcision; Sealing; Holy Spirit; Baptism